Triethylamine sensor of carnosine-perylene diimide supramolecular material constructed based on self-assembly method, and preparation method and application thereof
By using a triethylamine sensor based on a self-assembly method constructed by a carnosine-perylene diimide supramolecular material at room temperature, the problem of difficulty in detecting triethylamine at room temperature is solved in the prior art, and the problem of rapid and sensitive detection of triethylamine at room temperature is achieved. High sensitivity and fast response detection effect.
Patent Information
- Application Number
- CN202411541457.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The prior art is difficult to quickly and sensitively detect the content of triethylamine in the solution at room temperature, and the high operating temperature of the sensor and the high cost of use of precious metals.
Carnosine-perylene diimide supramolecular material constructed based on self-assembly method is used as the triethylamine sensor, and ITO glass is used as the working electrode. The supramolecular material is applied to the surface of the ITO glass by drop coating to form a sensor, and the Test at room temperature.
It realizes the rapid and sensitive detection of the content of triethylamine in the solution at room temperature. The sensor has the advantages of high sensitivity, fast response, simple preparation process, good stability, and no safety hazards.
Smart Images

Figure CN119413862A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of organic semiconductor sensors, and in particular relates to a triethylamine sensor of carnosine-perylene diimide supramolecular nanomaterial constructed based on a self-assembly method, and a preparation method and application thereof. Background Art
[0002] The boiling point of triethylamine (TEA) at room temperature and pressure is 89.5°C. It has been widely used in many fields, such as agriculture, fishery, aviation, medicine and health. It is also an important raw material for industrial development. It is an excellent solvent, polymer inhibitor and preservative, but it is also a substance that harms human health. The harm of triethylamine to the human body is mainly manifested in strong stimulation to the skin, mucous membranes and central nervous system. Therefore, for industrial safety and human health, it is urgent to prepare a sensor that can detect triethylamine instantly and sensitively. At present, most of the sensors for detecting triethylamine are gas sensors based on resistance, and there are fewer means for directly detecting triethylamine in liquid state. In chemical experiments, industrial production and daily life, there is a situation where triethylamine is present in the solution.
[0003] The detection methods of triethylamine mainly include gas chromatography-mass spectrometry (GC-MS), high performance liquid chromatography, and infrared spectroscopy (IR). Although gas chromatography-mass spectrometry and high performance liquid chromatography have good separation effect and high accuracy, they have high requirements for equipment and analytical technology, complicated steps, expensive, laborious and time-consuming, and the working temperature is very high during the detection process. Although infrared spectroscopy is simple to operate, it has low accuracy and is easily interfered by other organic substances. The gas sensor for detecting triethylamine generally has the disadvantages of high working temperature and wrong response to humidity changes. At present, the sensor for detecting triethylamine is mainly a semiconductor metal oxide gas sensor, which uses transition metal doping and noble metal loading to improve the gas-sensitive performance of semiconductor metal oxides, thereby improving responsiveness and selectivity. For example, patent CN118191038A prepares a triethylamine sensor of In2O3 nanosphere sensitive material with Au loading and Nd doping, but the problem of high working temperature still exists. The working temperature of these gas-sensitive materials is usually above 250°C, and the price of noble metals is too high to be conducive to practical application. Summary of the invention
[0004] The purpose of the present invention is to provide a triethylamine sensor based on a carnosine-perylene diimide supramolecular material constructed by a self-assembly method, a preparation method and use thereof. The sensor can be used to detect trace triethylamine at room temperature, and has the advantages of simple preparation process, good stability and high detection sensitivity.
[0005] The technical solution for achieving the purpose of the present invention is as follows:
[0006] A triethylamine sensor based on a carnosine-perylene diimide supramolecular material constructed by a self-assembly method, wherein ITO glass is used as a working electrode, and a supramolecular material is coated outside an ITO film on the surface of the ITO glass to form the sensor, wherein the supramolecular material is an amphiphilic carnosine-perylene diimide derivative, referred to as CPe, and has the structural formula:
[0007]
[0008] The preparation method of the triethylamine sensor of the carnosine-perylene diimide supramolecular material constructed based on the self-assembly method comprises the following steps:
[0009] S1, preparing a CPe self-assembly material solution with a concentration of 0.05-0.8 mM;
[0010] S2, dripping the CPe self-assembly material solution onto the ITO film surface of the cleaned ITO glass by drop coating, with the dripping amount being 0.1-0.2 mL per square centimeter;
[0011] S3, after the solvent evaporates at room temperature, vacuum dry at 35-65°C for 24-72h to obtain the sensor.
[0012] Furthermore, step S1 includes the following sub-steps:
[0013] S1-1, dissolving CPe solid in chloroform to a concentration of 1.0-20.0 mM, and ultrasonicating for 10-30 min to obtain a mother solution;
[0014] S1-2, take 200-2000 μL of the mother solution into a vial, dry it under N2 protection, and then dry it under vacuum at 35-65°C for 48-72 hours;
[0015] S1-3, taking the solid dried in step S1-2, dissolving it in tetrahydrofuran, stirring at 45-55°C for 3-5h, then lowering the temperature to 35°C, stirring for 0.5-2h, and obtaining a clear and transparent sample with a concentration of 0.5-4mM;
[0016] S1-4, taking the solution after step S1-3, diluting it with tetrahydrofuran, sonicating it for 5 to 20 minutes, and then adding water and sonicating it for 5 to 20 minutes to obtain a CPe self-assembly material solution, wherein the CPe concentration is 0.05 to 0.8 mM. The volume ratio of tetrahydrofuran to aqueous solution is preferably 3 / 7.
[0017] In step S2, the supramolecular material is coated on the ITO glass surface in an area of 1×1 cm 2 .
[0018] The cleaning method in step S2 is to ultrasonically clean the ITO glass with toluene, acetone and anhydrous ethanol of different polarities for five minutes in sequence, and clean it three times with each solvent, and then vacuum dry it for standby use.
[0019] The sheet resistance of the ITO glass after the cleaning process in step S2 is <7 ohm / sq.
[0020] The purpose of the triethylamine sensor based on the self-assembly method-based carnosine-perylene diimide supramolecular material is that it can be used for the sensing test of triethylamine, and the test steps are as follows:
[0021] (1) The prepared sensor was fixed in an electrolyte as a working electrode, a saturated calomel electrode was used as a reference electrode, and a platinum electrode was used as a counter electrode. The working electrode was connected to an electrochemical workstation to record the photocurrent value in the dark state.
[0022] (2) drawing a prescribed amount of triethylamine, injecting it into the closed electrolytic cell, turning on the light source, and recording the photocurrent change value of the sensor;
[0023] (3) After the set time is reached, turn off the light source, wait for the same time, turn on the light source again, and record the change in the photocurrent of the sensor;
[0024] (4) exporting the photocurrent data collected by the electrochemical workstation, taking time as the abscissa and the photocurrent change value as the ordinate, to obtain a curve of the photocurrent change over time at different triethylamine contents, and after processing, obtaining a triethylamine response curve related to triethylamine and photocurrent;
[0025] (5) Under the same conditions as in step (4), namely, the light power density is 236-240 mW / cm2, the bias voltage is 0.5 V, the light source distance is 3 cm, and the temperature is room temperature, the sensor is placed in the triethylamine electrolyte to be tested, and the triethylamine content is obtained by the triethylamine response curve obtained in step (4) through the photocurrent change value.
[0026] The electrolyte in step (1) is 8 mL of 0.1-0.3 M sodium sulfate aqueous solution. The light source used is a 250W / 350W xenon lamp with a wavelength range of >420nm and a light power density of 236-240mW / cm 2 , the bias voltage was 0.5 V, the light cycle was 40 s, the single test time was 200 s, the side of the ITO glass working electrode with the CPe self-assembly material solution was facing the incident light source, and the light source distance was 3 cm.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] 1. The carnosine-perylene diimide derivative (CPe) in the present invention has both hydrophilic and hydrophobic amphiphilicity and donor-acceptor structure. The former helps to regulate the molecular arrangement inside the nanomaterial by using different solvent compositions and construct a long-range ordered and morphologically diverse assembly structure, while the latter can form an effective internal electric field in the assembly structure. The two work together to achieve efficient transport of photogenerated carriers, inhibit charge recombination, and promote the charge separation of photogenerated electrons and holes, thereby improving its photoelectric responsiveness. In addition, the present invention utilizes the introduction of chiral carnosine to induce CPe to self-assemble into a more long-range ordered and supramolecular chiral assembly material through chiral transfer and amplification, further improving the carrier mobility, thereby enhancing the sensitivity of the sensor. Studies have shown that the sensor constructed with CPe assembly material has a maximum photoresponse current value of up to 95.0μA / cm to triethylamine. 2 , the light-dark ratio is 38, and the detection limit of triethylamine is as low as 11.8ppm.
[0029] 2. The triethylamine sensor has the advantage of being able to quickly and effectively determine the content of triethylamine in a solution at room temperature without any safety hazards, and has broad application prospects in detecting trace triethylamine content in a solution. In addition, the sensor is prepared by fixing the sensing film on the ITO glass by a simple drop coating method, which is simple and has good processability, and has the advantages of high sensitivity and fast response. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The process flow chart of using the supramolecular material formed by self-assembly of amphiphilic carnosine-perylene diimide derivatives as a sensor for detecting triethylamine.
[0031] Figure 2 (a) Digital images of CPe assemblies under natural light and 365nm UV light, (b) UV-visible absorption spectrum, (c) fluorescence emission spectrum, and (d) circular dichroism spectrum in mixed solvents with different THF / water ratios. The excitation wavelength of the fluorescence spectrum is 483nm and the CPe concentration is 0.05mM.
[0032] Figure 3 (a) Cyclic photocurrent response and (b) photocurrent variation curve of CPe drop-cast films constructed at different tetrahydrofuran / water ratios. The inset is a macroscopic image of the CPe drop-cast film before and after the experiment. The CPe concentration is 0.5 mM.
[0033] Figure 4 TEM images (af) and SEM images (gi) of CPe assemblies. The volume ratios of water / tetrahydrofuran are 5 / 5, 6 / 4, and 7 / 3 from left to right. The inset is the diameter distribution and corresponding histogram of the CPe assemblies. The CPe concentration is 0.05 mM.
[0034] Figure 5(a) UV-visible absorption spectra, (b) fluorescence emission spectra, (c) circular dichroism spectra, and (d) CPe assemblies at different triethylamine contents. water =0.7, CPe concentration is 0.05mM.
[0035] Figure 6 (a, b) Cyclic photocurrent response of CPe drop-cast film to different contents of triethylamine, (c, d) Response curve, the tetrahydrofuran / water mixed solvent component for preparing the assembled material is f water =0.7(a), f water =0(b), CPe concentration is 0.5 mM.
[0036] Figure 7 The real-time cyclic photocurrent response of CPe drop-cast film to different contents of triethylamine. The components of the tetrahydrofuran / water mixed solvent for preparing the assembled material are (a)f water =0.7, (b)f water =0, CPe concentration is 0.5 mM. DETAILED DESCRIPTION
[0037] The present invention is further described in detail below in conjunction with specific embodiments and drawings, but the embodiments of the present invention are not limited thereto.
[0038] Synthesis route of amphiphilic carnosine-perylene diimide derivatives (CPe):
[0039] (1) 2-3 g of 12-tricosanone, 4-5 g of ammonium acetate, and 1-2 g of sodium cyanoborohydride are added to 100-150 mL of isopropanol, and stirred for 4 days. Then, 1-2 mL of concentrated hydrochloric acid is added, and the mixture is rotary evaporated. After adding a potassium hydroxide aqueous solution, the mixture is washed with dichloromethane and rotary evaporated to obtain 12-tricosanamine.
[0040] (2) adding the 12-tricosaneamine and perylene anhydride prepared in step (1) to imidazole, stirring at high temperature for 6 to 8 hours to obtain a red product, perylene-3,4,9,10-tetracarboxylic dianhydride.
[0041] (3) Add the red product perylene-3,4,9,10-tetracarboxylic dianhydride prepared in step (2) and potassium hydroxide to 30-50 mL of tert-butyl alcohol, stir at high temperature for 1-3 hours, add acetic acid after the solution is cooled, react for 2-3 hours, purify, and filter under reduced pressure to obtain a crude product. After separation and purification by chromatography, the product N-(1-diundecyl)-3,4,9,10-perylenetetracarboxylic acid monoimide is obtained.
[0042] (4) Taking N-(1-diundecyl)-3,4,9,10-perylenetetracarboxylic acid monoimide as a precursor, the precursor and carnosine were dissolved in imidazole at 135°C, and then heated to 160°C and stirred for 5 hours. The mixture was cooled to 80°C, stirred with HCl solution for 2 hours, filtered, and the filter cake was washed with dichloromethane for 3-5 times, and vacuum dried at 60°C for 48 hours to obtain an amphiphilic carnosine-perylene diimide derivative, whose structural formula is:
[0043]
[0044] The preparation method of the triethylamine sensor based on the carnosine-perylene diimide supramolecular material constructed by the self-assembly method is carried out according to the following steps:
[0045] S1, preparing a CPe self-assembly material solution with a concentration of 0.05-0.8 mM; comprising the following steps:
[0046] S1-1, dissolving CPe solid in chloroform to a concentration of 1.0-20.0 mM, and ultrasonicating for 10-30 min to obtain a mother solution;
[0047] S1-2, take 200-2000 μL of the mother solution into a vial, dry it under N2 protection, and then dry it under vacuum at 35-65°C for 48-72 hours;
[0048] S1-3, taking the solid dried in step S1-2, dissolving it in tetrahydrofuran, stirring at 45-55°C for 3-5h, then lowering the temperature to 35°C, stirring for 0.5-2h, and obtaining a clear and transparent sample with a concentration of 0.5-4mM;
[0049] S1-4, taking the solution after step S1-3, diluting it with tetrahydrofuran, ultrasonicating it for 5 to 20 minutes, and then adding water and ultrasonicating it for 5 to 20 minutes to obtain a CPe self-assembly material solution, wherein the CPe concentration is 0.05 to 0.8 mM.
[0050] S2, dripping the CPe self-assembly material solution onto the ITO film surface of the cleaned ITO glass by drop coating, wherein the cleaning method is to ultrasonically clean the ITO glass with toluene, acetone and anhydrous ethanol of different polarities for five minutes, and each solvent is used for cleaning three times, and then vacuum drying; the amount of CPe self-assembly material solution dripped is 0.1-0.2 mL per square centimeter; the coating area of the supramolecular material on the ITO glass surface is 1×1 cm 2 The square resistance of the cleaned ITO glass is <7ohm / sq.
[0051] S3, after the solvent evaporates at room temperature, vacuum dry at 35-65°C for 24-72h to obtain the sensor.
[0052] The triethylamine sensor based on the self-assembly method of carnosine-perylene diimide supramolecular material is used for the sensing test of triethylamine. The test steps are as follows:
[0053] (1) The prepared sensor was fixed in an electrolyte as a working electrode, a saturated calomel electrode as a reference electrode, and a platinum electrode as a counter electrode. The working electrode was connected to an electrochemical workstation, and the electrochemical workstation type was VMP316 channel. The photocurrent value was recorded in the dark state. The electrolyte was 8 mL of 0.1-0.3 M sodium sulfate aqueous solution.
[0054] (2) A prescribed amount of triethylamine is absorbed and injected into the closed electrolytic cell, and the light source is turned on. The light source is a 250W / 350W xenon lamp with a wavelength range of >420nm and an optical power density of 236-240mW / cm 2 , bias voltage is 0.5V, light cycle is 40s, single test time is 200s, the side of the ITO glass working electrode dripped with CPe self-assembly material solution faces the incident light source, and the light source distance is 3cm. Record the photocurrent change value of the sensor.
[0055] (3) After the set time is reached, turn off the light source, wait for the same amount of time, turn on the light source again, and record the change in the photocurrent of the sensor.
[0056] (4) The photocurrent data collected by the electrochemical workstation are exported, with time as the horizontal axis and the photocurrent change value as the vertical axis, so as to obtain a curve of the photocurrent change over time at different triethylamine contents. After processing, a triethylamine response curve related to triethylamine and photocurrent is obtained.
[0057] (5) Under the same conditions as in step (4), namely, the light power density is 236-240 mW / cm2, the bias voltage is 0.5 V, the light source distance is 3 cm, and the temperature is room temperature, the sensor is placed in the triethylamine electrolyte to be tested, and the triethylamine content is obtained by the triethylamine response curve obtained in step (4) through the photocurrent change value.
[0058] Example 1
[0059] The specific implementation process is as follows Figure 1 As shown:
[0060] (1) Preparation of supramolecular self-assembly materials: Take 1.4 mL of chloroform to dissolve CPe solid to a concentration of 5.0 mM, and ultrasonicate for 30 min to obtain the mother liquor. Take 400 μL of the mother liquor to a vial, dry it under N2 protection, and then dry it under vacuum at 65°C for 48 h. Dissolve the dried solid in 800 μL of tetrahydrofuran, stir it for 3 h at 45°C, then lower the temperature to 35°C and stir it for 1 h to obtain a clear and transparent solution with a concentration of 2.5 mM. Take 200 μL of the solution, add 100 μL of tetrahydrofuran to dilute it, ultrasonicate for 5 min, and then add different volumes of water to ultrasonicate for 5 min to obtain a series of assembly solutions with different tetrahydrofuran / water solution volume ratios and a CPe concentration of 0.5 mM.
[0061] (2) Preparation of sensor: The assembly solution containing the amphiphilic carnosine-perylene diimide derivative nanomaterial is dropped onto the surface of the working electrode ITO by drop coating, with the drop amount being 0.1 mL per square centimeter. After the solvent evaporates, the solution is vacuum dried to obtain the sensor.
[0062] (3) Drawing a triethylamine response curve: placing the sensor in a triethylamine electrolyte with a known concentration, detecting the change of the photocurrent over time, and obtaining a triethylamine response curve.
[0063] (4) Detection of triethylamine content: In step (3), the optical power density is 236 mW / cm 2 Under the same conditions of bias voltage of 0.5 V, light source distance of 3 cm and room temperature, the sensor is placed in the triethylamine electrolyte to be tested, and the triethylamine content is obtained by the triethylamine response curve obtained in step (3) through the photocurrent change value.
[0064] Example 2
[0065] Example 2 studied the effect of different tetrahydrofuran / water solution volume ratios on CPe assembly.
[0066] The preparation of CPe assembly mother solution was the same as in Example 1. 200 μL of mother solution was taken, 100 μL of tetrahydrofuran was added to dilute, and after ultrasonication for 5 min, different volumes of water were added to ultrasonicate for 5 min to obtain assembly solutions with different tetrahydrofuran / water solution volume ratios of 0 to 0.9 and CPe concentration of 0.05 mM. After stabilization for 2 hours, the ultraviolet absorption spectrum was obtained by ultraviolet visible absorption spectrometer (Cary 5000, Varian, USA) with the slit width set to 5 nm and the optical path length set to 0.5 cm ( Figure 2 b) Using a fluorescence spectrometer (F-7000, Hitachi, Japan), the slit width was set to 2.5 nm, the excitation wavelength was set to 483 nm, and the optical path was set to 1 cm to test the fluorescence emission spectrum of the assembled solution ( Figure 2c) Using a circular dichroism spectrometer (J-810, JASCO, Japan), the response time was set to 4 s, the bandwidth was 2 nm, and the optical path was 0.5 cm to test the circular dichroism of the assembled solution ( Figure 2 d).
[0067] Depend on Figure 2 It can be seen that with the increase of water content in different tetrahydrofuran / water ratios, the color of the solution gradually changes from red to bright orange and then to red under natural light. Under the excitation of 365nm ultraviolet light, the fluorescence of the solution gradually increases, then weakens, and the color changes from fluorescent green to orange and then to red again. With the increase of water content, the maximum absorption peak of the assembly blue shifts, accompanied by peak broadening, indicating that the increase in water content causes the CPe assembly to transform from a monomer to an H-type aggregate. The fluorescence intensity first increases and then decreases. When the water content is 0.7, the fluorescence intensity reaches the minimum value, indicating that when the water content is 0.7, the degree of π-π stacking reaches the maximum. The CD signal shows a trend of first increasing, then decreasing, and then increasing. The change of the CD signal is similar to the trend of the ultraviolet absorption peak. When the water content reaches about 0.7, the CD signal is the strongest, indicating that the supramolecular chirality of the CPe assembly is the strongest.
[0068] Example 3
[0069] Example 3 studies the response of the drop-cast film made from the CPe assembly solution to the photocurrent at different tetrahydrofuran / water solution volume ratios.
[0070] The preparation of CPe assembly mother solution is the same as in Example 1. Take 200 μL of mother solution, add 100 μL of tetrahydrofuran to dilute, ultrasonicate for 5 minutes, add different volumes of water for 5 minutes, and obtain assembly solutions with different tetrahydrofuran / water solution volume ratios of 0 to 0.85 and CPe concentration of 0.5 mM. Take 100 microliters of solution with a pipette, evenly drop it on the ITO glass, and vacuum dry it at 65°C for 24 hours. At room temperature, use a standard three-electrode system to measure the photocurrent through an electrochemical workstation (VMP3 16channel, Biologic, Germany), using 0.1M sodium sulfate aqueous solution as the electrolyte, and the side of the ITO glass working electrode with the CPe self-assembly material solution facing the incident light source. The light source is a 250W / 350W xenon lamp (BBZW-III, wavelength range > 420nm), the bias voltage is set to 0.5V, the light cycle is 40s, the single test time is 200s, and the optical power density is 236-240mW / cm 2 , the distance between the lamp and the working electrode is 3 cm. The prepared sensor is used as the working electrode, the saturated calomel electrode is used as the reference electrode, and the platinum electrode is used as the counter electrode. Turn on the light source, make the light path perpendicular to the sample surface, and record the photocurrent data.
[0071] Depend on Figure 3It can be seen that as the water content in different THF / water ratios increases, the photoelectric performance increases accordingly. (b) The inset in the figure is a state diagram of the sample on the ITO glass before and after the test. It can be seen that before and after the test, the CPe drop-cast film remains intact without falling off, and when the water content is about 0.7, the film-forming property of the CPe drop-cast film is good. When the water content is greater than 0.7, the drop-cast film may fall off.
[0072] Example 4
[0073] Example 4 studies the morphological changes of CPe assemblies at different tetrahydrofuran / water solution volume ratios.
[0074] The preparation of CPe assembly mother solution was the same as in Example 1. 200 μL of mother solution was taken, 100 μL of tetrahydrofuran was added for dilution, and after ultrasonication for 5 min, different volumes of water were added for ultrasonication for 5 min to obtain assembly solutions with different tetrahydrofuran / water solution volume ratios of 0.5, 0.6, and 0.7, respectively, and a CPe concentration of 0.05 mM.
[0075] Depend on Figure 4 It can be seen that with the increase of water content in different tetrahydrofuran / water ratios, the morphology of the assembly gradually changes from the coexistence of larger short rods and "donut" structures to smaller nanomaterials dominated by "donut" structures.
[0076] Example 5
[0077] Example 5 studies the effect of different triethylamine contents on CPe assembly when the water content is 0.7.
[0078] The preparation of the CPe assembly mother solution was the same as in Example 1. 200 μL of the mother solution was taken, 100 μL of tetrahydrofuran was added for dilution, and after ultrasonication for 5 minutes, a certain volume of water was added for ultrasonication for 5 minutes to prepare a 0.05 mM clear and transparent assembly solution with a tetrahydrofuran / water volume ratio of 3 / 7. Different volumes of triethylamine were added to the solution, stabilized for 5 minutes, and then tested.
[0079] Depend on Figure 5It can be seen that with the increase of triethylamine content, the maximum absorption peak of CPe assembly becomes narrower and the intensity increases, indicating that the degree of π-π stacking is weakened, the fine structure gradually appears, and the fluorescence intensity also increases. The CD signal shows a trend of first rising and then falling. When the molar ratio of triethylamine to CPe assembly reaches 5:1, the CD signal is the strongest, indicating that the supramolecular chirality of CPe assembly is the strongest at this time. The above results show that the addition of a small amount of triethylamine helps to further improve the long-range order and supramolecular chirality of the assembly structure, while the addition of excessive triethylamine induces the disintegration of the supramolecular material structure into oligomers and single molecules. In the triethylamine detection system, the disintegration of supramolecular materials was not observed, so it mainly reflects that triethylamine optimizes the order of supramolecular materials, and the improvement of order helps to further improve the photoelectric responsiveness.
[0080] Example 6
[0081] Example 6 studies the response of different contents of triethylamine to the photocurrent when the water content is 0.7 and 0.
[0082] The preparation of the CPe assembly mother solution is the same as in Example 1. Take 200 μL of the mother solution, add 100 μL of tetrahydrofuran to dilute, ultrasonicate for 5 minutes, add different volumes of water for 5 minutes, prepare a 0.5 mM clear and transparent assembly solution with a water content of 0.7 and 0, add different volumes of triethylamine to the solution, and stabilize for 5 minutes. Take 100 microliters of the solution with a pipette, evenly drop it on the ITO glass, and vacuum dry it at 65°C for 24 hours. At room temperature, use a standard three-electrode system to measure the photocurrent through an electrochemical workstation, using the prepared sensor as the working electrode, a saturated calomel electrode as the reference electrode, and a platinum electrode as the counter electrode. Turn on the light source so that the light path is perpendicular to the sample surface, record the photocurrent data, turn off the light source after 20 seconds, wait for 20 seconds and turn on the light source again, and repeat 2 times. Select 15 points in the triethylamine content of 0vol / %-2.5vol / %, and repeat the above process. The electrochemical workstation can be used to obtain a curve of photocurrent versus time at different triethylamine contents. The triethylamine response curve is obtained by plotting the triethylamine as the horizontal coordinate and the photocurrent as the vertical coordinate.
[0083] Depend on Figure 6 It can be seen that when the triethylamine content is lower than 2.5 vol / %, the photocurrent increases with the increase of triethylamine content. When the triethylamine content is higher than 2.5 vol / %, the increase of photocurrent reaches a platform, and the smaller the triethylamine content, the more significant the change of photocurrent, indicating that the sensor has a high sensitivity to the detection of trace triethylamine. The drop-cast film prepared by the assembly solution with a tetrahydrofuran / water solution volume ratio of 3 / 7 is used as a sensor, and the strongest photoresponse current value to triethylamine is as high as 95.0 μA / cm 2 , the light-dark ratio is 38, and the detection limit of triethylamine is as low as 11.8ppm.
[0084] Example 7
[0085] Example 7 studies the response of online addition of different amounts of triethylamine to the photocurrent when the water content is 0.7 and 0.
[0086] This embodiment is substantially the same as embodiment 6, except that different amounts of triethylamine were added during the photocurrent test. After adding a trace amount of triethylamine (0.06 vol / %), the light source was turned on and the photocurrent changed immediately. The drop-cast film prepared from the assembly solution with a tetrahydrofuran / water solution volume ratio of 3 / 7 as a sensor was more responsive to triethylamine.
[0087] The present invention is not limited to the above-mentioned embodiments. On the basis of the technical solution disclosed in the present invention, technicians in this field can make some substitutions and deformations to some technical features therein according to the disclosed technical content without creative labor, and these substitutions and deformations are all within the protection scope of the present invention.
Claims
1. A triethylamine sensor based on carnosine-perylene diimide supramolecular material constructed by self-assembly method, characterized in that: ITO glass is used as a working electrode, and a supramolecular material is coated outside the ITO film on the surface of the ITO glass. The supramolecular material is an amphiphilic carnosine-perylene diimide derivative, referred to as CPe, and its structural formula is:
2. The method for preparing a triethylamine sensor based on the self-assembly method of carnosine-perylene diimide supramolecular material according to claim 1, characterized in that: The steps include: S1, preparing a CPe self-assembly material solution with a concentration of 0.05-0.8 mM; S2, dripping the CPe self-assembly material solution onto the ITO film surface of the cleaned ITO glass by drop coating, with the dripping amount being 0.1-0.2 mL per square centimeter; S3, after the solvent evaporates at room temperature, vacuum dry at 35-65°C for 24-72h to obtain the sensor.
3. The method for preparing a triethylamine sensor based on the self-assembly method of carnosine-perylene diimide supramolecular material according to claim 2, characterized in that: Step S1 includes the following sub-steps: S1-1, dissolving CPe solid in chloroform to a concentration of 1.0-20.0 mM, and ultrasonicating for 10-30 min to obtain a mother solution; S1-2, take 200-2000 μL of the mother solution into a vial, dry it under N2 protection, and then dry it under vacuum at 35-65°C for 48-72 hours; S1-3, taking the solid dried in step S1-2, dissolving it in tetrahydrofuran, stirring at 45-55°C for 3-5h, then lowering the temperature to 35°C, stirring for 0.5-2h, and obtaining a clear and transparent sample with a concentration of 0.5-4mM; S1-4, taking the solution after step S1-3, diluting it with tetrahydrofuran, ultrasonicating it for 5 to 20 minutes, and then adding water and ultrasonicating it for 5 to 20 minutes to obtain a CPe self-assembly material solution, wherein the CPe concentration is 0.05 to 0.8 mM.
4. The method for preparing a triethylamine sensor based on the self-assembly method-based carnosine-perylene diimide supramolecular material according to claim 3, characterized in that: In step S1-4, the volume ratio of tetrahydrofuran / water solution is 3 / 7.
5. The method for preparing a triethylamine sensor based on the self-assembly method-based carnosine-perylene diimide supramolecular material according to claim 2, characterized in that: In step S2, the supramolecular material is coated on the ITO glass surface in an area of 1×1 cm 2 .
6. The method for preparing a triethylamine sensor based on the self-assembly method of carnosine-perylene diimide supramolecular material according to claim 2, characterized in that: The cleaning method in step S2 is to ultrasonically clean the ITO glass with toluene, acetone and anhydrous ethanol of different polarities for five minutes in sequence, and clean it three times with each solvent, and then vacuum dry it for standby use.
7. The use of a triethylamine sensor of a carnosine-perylene diimide supramolecular material constructed based on a self-assembly method according to claim 1, characterized in that: For the sensing test of triethylamine, the test steps are as follows: (1) The prepared sensor was fixed in an electrolyte as a working electrode, a saturated calomel electrode was used as a reference electrode, and a platinum electrode was used as a counter electrode. The working electrode was connected to an electrochemical workstation to record the photocurrent value in the dark state. (2) drawing a prescribed amount of triethylamine, injecting it into the closed electrolytic cell, turning on the light source, and recording the photocurrent change value of the sensor; (3) After the set time is reached, turn off the light source, wait for the same time, turn on the light source again, and record the change in the photocurrent of the sensor; (4) exporting the photocurrent data collected by the electrochemical workstation, taking time as the abscissa and the photocurrent change value as the ordinate, to obtain a curve of the photocurrent change over time at different triethylamine contents, and after processing, obtaining a triethylamine response curve related to triethylamine and photocurrent; (5) In step (4), the optical power density is 236-240 mW / cm 2 Under the same conditions of bias voltage of 0.5 V, light source distance of 3 cm and room temperature, the sensor is placed in the triethylamine electrolyte to be tested, and the triethylamine content is obtained by the triethylamine response curve obtained in step (4) through the photocurrent change value.
8. The use of a triethylamine sensor of a carnosine-perylene diimide supramolecular material constructed based on a self-assembly method according to claim 7, characterized in that: The electrolyte in step (1) is 8 mL of 0.1-0.3 M sodium sulfate aqueous solution.
9. The use of a triethylamine sensor of a carnosine-perylene diimide supramolecular material constructed based on a self-assembly method according to claim 7, characterized in that: The light source is a 250W / 350W xenon lamp with a wavelength range of >420nm and an optical power density of 236-240mW / cm 2 , the bias voltage was 0.5 V, the light cycle was 40 s, the single test time was 200 s, the side of the ITO glass working electrode with the CPe self-assembly material solution was facing the incident light source, and the light source distance was 3 cm.
Citation Information
Patent Citations
Super-molecular polypeptide with self-assembly aggregate structure and preparation method of preparation method of polypeptide
CN110123658A
Organic and inorganic composite film used for detecting triethylamine and gas-sensitive sensor
CN110274936A
Perylene tetracarboxylic acid diimide compound as well as preparation method and application thereof
CN110283173A
Perylene tetracarboxylic acid bisimide derivative, n-type semiconductor, a method for producing n-type semiconductor, and electronic device
US20140024171A1